2013
DOI: 10.1016/j.jped.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Motor Dysgraphia in Public Schools

Abstract: Given the large number of warning signs of dysgraphia observed in schoolchildren, it is advisable to screen for these signs, in order to implement early interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
14
0
3
Order By: Relevance
“…Researchers have suggested that handwriting difficulties may result in serious consequences for the student's overall academic success, emotional well-being, attitude, and behavior (Feder & Majnemer, 2007;Peverly et al, 2013). These findings reinforce the importance of identifying handwriting difficulties as early as possible, both as a preventive and as a corrective aid (Martins et al, 2013).…”
mentioning
confidence: 90%
“…Researchers have suggested that handwriting difficulties may result in serious consequences for the student's overall academic success, emotional well-being, attitude, and behavior (Feder & Majnemer, 2007;Peverly et al, 2013). These findings reinforce the importance of identifying handwriting difficulties as early as possible, both as a preventive and as a corrective aid (Martins et al, 2013).…”
mentioning
confidence: 90%
“…Such an impairment of the neuro-muscular system can have serious pedagogical and psychological consequences, and can greatly affect a child's every-day life [12] starting with slow and less-legible handwriting, lack of motivation to write, lower self-esteem combined with poor emotional well-being, bad attitude and behaviour, communication and social interaction problems, and in some cases going as far as being diagnosed with a serious neurodevelopmental disorder such as developmental dysgraphia (DD) [9], [13]- [15]. To provide children with both preventive as well as corrective therapeutic care, GD should be identified and treated as soon as possible [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the ADHD group had poorer motor planning and execution skills and greater variability in motor control than the control subjects. Li-Tsang et al [22] suggested that handwriting assessment can effectively distinguish children with ADHD or ADHD with learning disorders (ADHD-LD) from control subjects by the degree of variation in speed of writing or pen pressure.…”
Section: Discussionmentioning
confidence: 99%